Angiotomography - 3D and aneurisms microsurgery: preliminary report - Ramírez, Julio (2003)
OBJECTIVE: To determine if cerebral pan-angiography with conventional digital substraction and AngioTac-3D allow tridimensional visualization of aneurisms in patients with acute subarachnoid hemorrhage (ASH) due to rupture of an aneurism. MATERIAL AND METHODS: We present the first 10 cases of men and women who were admitted with either acute or “late” ASH to whom cerebral pan-angiography with conventional digital substraction and 3D-AngioTac were performed followed by microsurgery. RESULTS: Use of tridimensional angiotomography with surface reconstruction allows us to see vascular, venous and bony structures, rotating them in 360 degrees. It follows the need that the neurosurgeon be present during the procedure in order that images lead the surgical criterium. CONCLUSION: The non-invasive tridimensional angiotomography allows diagnosis of subarachnoid hemorrhage, as seen in these preliminary report.